Local Tourists’ Perceptions on City Rejuvenation, Destination Image, City Brand Identity and Intention to Recommend Johannesburg, South Africa - Sehahabane, Puseletso; Chuchu, Tinashe; Maziriri, Eugine Tafadzwa (Graduate School, Universitas Brawijaya, 2023)
Destination marketing, as a concept, has received much attention in tourism research. This research investigates the relationship between constructs, including city rejuvenation, destination image, city brand identity, and city perceptions. The study was quantitative in nature, adopting the survey method. A unique conceptual model was developed to test proposed hypotheses based on the abovementioned constructs. Data was collected from Braamfontein, a busy business district of Johannesburg, South Africa. A total of 297 participants completed the survey, and these responses were processed in SPSS 24 and AMOS 24 for descriptive statistics and hypotheses testing, respectively. The outcome (intention to recommend) was tested against three constructs (city brand identity, destination image, and city perception. The key finding suggests that destination image has the strongest influence on the intention to recommend a destination. This implies that the most significant incentive for tourists to recommend a destination is mainly caused by the traveller's perception of the destination's image. Based on the implications of the findings, further research direction is proposed. Keywords: City Brand Identity, City Perceptions, City Rejuvenation, Destination Image.